Development of Immunochromatographic Assay for the Rapid Detection of Mycoplasma capricolum subsp. capripneumoniae Antibodies - Zhu, Zhen; Qu, Guanggang; Wang, Changjiang; Wang, Lei; Du, Jige; Li, Qianlin; Shen, Zhiqiang; Chen, Xiaoyun (Frontiers in Microbiology, 2022)
Mycoplasma capricolum subsp. Capripneumoniae (Mccp) is the cause of contagious caprine pleuropneumonia (CCPP) that is a highly contagious respiratory disease in goat leading to significant economic losses in Africa and Asia. Current available procedures for the diagnosis of CCPP have some limitations in sensitivity, specificity, operation of time, requirement of sophisticated equipment or skilled personnel and cost involvement. In this study, we developed a rapid, sensitive and specific colloidal gold-based immunochromatographic assay (GICA) strip for the efficient on-site detection of Mccp serum antibodies within 10 min. For the preparation of this colloidal GICA strip, recombinant P20 protein, the membrane protein of M. capricolum subsp. capripneumoniae, was expressed by E.coli prokaryotic expression system and used as the binding antigen in the test line after purification. The rabbit anti-goat IgG labeled with the colloidal gold was used as the detection probe and goat anti-rabbit IgG was coated on the nitrocellulose membrane as the control line, respectively. The concentration of the coating antibody was optimized and the effectiveness of this colloidal GICA strip was evaluated. Our results proved that the detection limit of the test strip was up to 1:64 dilutions for the Mccp antibody positive serum samples with no cross-reactivity with other pathogens commonly infecting small ruminants，including goat pox virus, peste des petits ruminants virus, foot-and mouth disease virus type A or other mycoplasmas. Moreover, the colloidal GICA strip was more sensitive and specific than indirect hemagglutination assay (IHA) for the detection of Mccp serum antibody. 106 clinical serum samples were detected by the colloidal GICA strip compared to complement fixation test (CFT), demonstrating an 87.74% concordance with the CFT. This novel colloidal GICA strip would be an effective tool for the cost-effective and rapid diagnosis of CCPP in the field.